Bias in Estimations of DNA Content by Competitive Polymerase Chain Reaction - Alvarez, Mariano J. (2000)
Competitive PCR is a highly sensitive method for specific DNA quantification. Despite the lack of studies related to the accuracy of the method it has been widely used. Here we present a simulation model for competitive PCR, which takes into account the efficiency decay as a linear relationship of the total product yield. The model helped us to study the kind and magnitude of errors that arise from quantitative and semiquantitative competitive PCR protocols and to find ways to minimize them. The simulation data suggest that differences in amplification efficiency between target and standard templates induce stronger biases in quantitative than in semiquantitative competitive PCR. Quantitative competitive PCR can only be used when both efficiencies are equal. In contrast, semiquantitative competitive PCR can be used even when the target is amplified with a higher efficiency than the standard, since under such conditions the method tends to underestimate the differences in initial DNA content. These predictions have been confirmed with experimental data and show that the estimation of the amplification efficiencies is a prerequisite for the use of quantitative and semiquantitative competitive PCR. A simple method for this estimation is also presented.